MODEL VEKTOR AUTOREGRESSIVE UNTUK PERAMALAN CURAH HUJAN DI INDRAMAYU (Vector Autoregressive Model for Forecast Rainfall In Indramayu ) - Dewi Retno Sari Saputro; Aji Hamim Wigena; Anik Djuraidah (FORUM STATISTIKA DAN KOMPUTASI, 2011)
There are three regions of rainfall that has been formed, each rainfall regions has a variety of homogeneous and there is a correlation between rainfall stations. In each region can be determined rainfall prediction model simultaneously. The model is a model of Vector Autoregressive (VAR) which is an extension of the autoregressive model (AR). Based on this research, we can determine the VAR model by lag 1 or VAR (1) for each region. Region 1 (Anjatan and Sumurwatu), region 2 (Salamdarma and Gantar) and region 3 (Kedokan Bunder and Sudimampir), each of which has a Root Mean Square Error Prediction (RMSEP) of 3.93; 5:03; 4:48; 5.3; 2:18 and 3:53. Correlation value of observations with predictions of rainfall respectively, 0.71; 0.62; 0:57; 0:59; 0.89, and 0.91. Keywords: AR, VAR, RMSEP, correlation